Ações de manutenção em Parques eólicos com recurso ao modelo estocástico - Ana Patrícia Lopes Miranda (2019)
The European Union has established that the production of electricity from renewable energy sources would aim to equal 20% of total energy consumption by 2020. However, on 30 November 2016, this target was revised and became 27% of energy consumed in 2030. According to data from WindEurope (European Wind Energy Association), wind power produced in 2018 is enought to supply 21% of the EU average daily consumption (about 2150 GWh). By 2020, in the EU, it is predicted that wind power plants, both onshore and offshore, will be the renewable technology with the highest increase in power (50 GW), followed by the photovoltaic (35 GW). In Portugal, wind power plants annually produce about 1/4 of the national electricity needs, allowing the country to reduce their imports of fossil fuels more than 350 M € per year. The maintenance of wind turbines takes now an extremely importance in maximizing the amount of energy produced by wind farms. The goal of this dissertation, concerns on the elaboration of a planning for the maintenance of onshore wind farms, based on a stochastic process, that explains the best strategy of preventive maintenance, minimizing the energy that is not produced, and for this, is taking into account the behavior of the speed of wind, asset reliability, inoperability by maintenance and wind turbine efficiency. The dissertation is being developed in a business environment on the portuguese promoter of wind farms, EDP Renováveis.